The Effectiveness of Music Therapy on Anxiety and Blood Pressure in Older People with Hypertension: A Literatur Review - Ni Putu Ayu Ratna Dewi; Ni Putu Kamaryati; I Kadek Nuryanto; Putu Inge Ruth Suantika (STIKep PPNI Jawa Barat, 2023)
Aims: As people get older, numerous cardiovascular disorders, including hypertension, which many older people have, will become more prevalent. Music therapy, as a non-pharmacological therapy, can be used to reduce blood pressure and anxiety in hypertensive patients. Objective: This literature review aims to determine the effectiveness of types music therapy that can reduce anxiety and blood pressure in the elderly with hypertension. Methods: To conduct a type of literature review, 10 articles that discuss the effectiveness of music therapy in lowering blood pressure and anxiety in hypertensive patients were searched for. The databases used are Pubmed, Google Scholar, and Science Direct, by entering keywords. The inclusion criteria used for data collection were full text, type of research (RCT, quasi-experimental, and pre-experimental), in English and Indonesian, and journal publishing from 2018 to 2023. Result: Ten relevant articles, including 505 respondents, were extracted in this study. Most of the studies (70%) showed significant results, showing that music therapy (traditional, classical, and spiritual) was effective in reducing high blood pressure and anxiety. Favorite music has a stronger effect than foreign music, such as traditional music, which has a deeper emotional impact on the elderly. Conclusion: Music therapy is effective in reducing blood pressure and anxiety in the elderly, and besides that, it is cost-effective and easy to use. Further research on the application of traditional music types is needed to determine the effectiveness of the music.